Analisis kualitas makanan terhadap kepuasan wisatawan di harris restaurant pada hotel harris raya kuta - Yorlanita Agustina Sojo; Ni Made Ariani; I Nyoman Tri Sutaguna (DIPLOMA IV TOURISM PROGRAM STUDY, TOURISM FACULTY,UDAYANA UNIVERSITY, 2020)
Abstract This Research was motivated by the complains submitted by tourists regarding the quality of food in Harris Restaurant at Harris Raya Kuta Hotel. The purpose of this research was findout food quality towards tourists satisfaction in Harris Restaurant at Harris Raya Kuta Hotel. The variable used in this research is quality of food and tourists satisfaction. The type of data in this research are qualitative and quantitative data, while the data sources used are primary data and secondary data. Method of collecting data are observation, interview, quitionare, documentation, and literature riview. Sampling technique uses quota sampling technique by determining the number of samples using the Slovin’s Formula and obtained as many as 100 samples. Technique of analyzing data used in this research are descriptive analysis and quantitative analysis consisting of descriptive statistical analysis by using a Likert Scale, inferensial statistical consisting of validity test, reliability test and important Performance Analysis.The result indicates that indicators that have given satisfaction to tourists are indicators of maturity level indicator, freshness to make food, portion, and texture. Then the rating of tourists on the quality of food in Harris Restaurant at Harris Raya Kuta Hotel obtained a score of 89,92% or tourists were satisfied with the quality of food in Harris Restaurant at Harris Raya Kuta Hotel. Key Word: Food Quality, Tourist Satisfaction, and restaurant.